Deforestation and child diet diversity: A geospatial analysis of 15 Sub-Saharan African countries. (May 2018) - Galway, Lindsay P.; Acharya, Yubraj; Jones, Andrew D.
Abstract: Deforestation worldwide could have important consequences for diet quality and human nutrition given the numerous ecosystem services that are provided by forests and biodiverse landscapes. Yet, empirical research assessing the links between deforestation and diets is lacking. In this study, we examined the association between deforestation and diet diversity among children using geolocated Demographic and Health Survey data for 33, 777 children across 15 countries of sub-Saharan Africa coupled with remotely-sensed data on forest cover loss. Deforestation was negatively associated with diet diversity (regression coefficient (95% CI): − 0.47 (− 0.76, − 0.18)), as well as recent consumption of legumes and nuts, flesh foods, and fruits and vegetables among children aged 6 months to 24 months. Regionally, these trends were statistically significant only in the West Africa region. This hypothesis-generating research adds to the growing body of evidence that forests and forest-based ecosystems are associated with diet quality and nutrition and provides support for future studies that examine mechanisms linking forest loss and human nutrition. Highlights: We assessed associations between deforestation (measured as forest loss) and child diets in SSA. Forest loss was negatively associated with child dietdiversity and consumption of nutritious food. The relationship between forest loss and child diet diversity was strongest in West Africa. Studies that examine the mechanisms linking deforestation and human nutrition are needed.